The Role of Optical Coherence Tomography in the Diagnosis of Angle Closed Diseases of the Anterior Chamber. Part 2: Visualization of the Posterior Segment of the Eye - N. I. Kurysheva; G. А. Sharova (Oftalʹmologiâ)
The purpose of this work is to review the literature data on the role of optical coherence tomography in the diagnosis of diseases of the closed angle of the anterior chamber. The analysis of the use of modern technical devices — optical coherence tomography of the posterior segment, models with a frequency-modulated source (Swept Source) is presented. The emergence of new imaging technologies such as SS-OCT contributes to understanding the pathogenesis of primary angle closure diseases in terms of involvement of the choroid in the process. A thicker choroid in the macular area may be an anatomical risk factor for closed angle disease. The expansion of an abnormally thick choroid in combination with the structural features of the anterior segment in eyes with a short axial length, including against the background of psychoemotional stress, can lead to an attack of angle closure. Visualization of the structures of the posterior segment of the eye is an important part of the strategy aimed at solving the problem of identifying risk factors, diagnosing, monitoring and evaluating the effectiveness of treatment of diseases of primary angle closure. Qualitative and quantitative data analysis based on optical coherence tomography significantly increases the diagnostic accuracy, allows to determine its progression and to predict its course. This plays a key role in the choice of treatment tactics for the anterior chamber angle closure. The review considers the effect of local antihypertensive eye drops on the choroid.Conclusion. Optical coherence tomography is a standard in modern diagnostics and evaluation of the effectiveness of treatment of diseases of primary angle closure, allowing a better understanding of the pathogenesis of the disease and its complex nature. Imaging improves the ability to accurately diagnose and choose the right treatment strategy.